A Brief Study on Energy in Itinerant-Electron Metamagnetic Materials at Very Low Temperature - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
Electronic energy is calculated explicitly for itinerant-electron metamagnetic materials at very low temperature. This calculation involves bandwidth and consequently volume, and it has been performed by means of an elliptic density of states. Moreover, total energy is considered.